From Monsters to Monuments: Reply to Manis - McIntosh, C. A. (Philosophia Christi, 2024)
I respond to R. Zachary Manis’s wide-ranging critique of the spectrum view of the imago Dei, and further explore the possibility that the damned are preserved for eternity not in a state of conscious suffering, but as monuments to the significance of the earthly travail.